2017
DOI: 10.1002/hep.29138
|View full text |Cite
|
Sign up to set email alerts
|

Substance P increases liver fibrosis by differential changes in senescence of cholangiocytes and hepatic stellate cells

Abstract: Substance P (SP) is involved in the proliferation of cholangiocytes in bile duct ligated (BDL) mice and human cholangiocarcinoma growth by interacting with the neurokinin-1 receptor (NK-1R). To identify whether SP regulates liver fibrosis during cholestasis, wild type (WT) or NK-1R knockout (NK-1R−/−) mice that received BDL or sham surgery and Mdr2−/− mice treated with either an NK-1R antagonist (L-733,060) or saline were used. Additionally, WT mice were treated with SP or saline intraperitoneally. In vivo, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
93
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 40 publications
6
93
0
Order By: Relevance
“…This study has also demonstrated that SP administration elevates intracellular cAMP levels followed by cell proliferation in large cholangiocytes suggesting that the SP/NK-1R axis is associated with large cholangiocyte proliferation. A recent study has shown that serum levels of SP and NK-1R expression in the liver are elevated in human PSC patients compared to healthy individuals [63]. In addition, SP administration induces bile duct hyperplasia and liver fibrosis in wild-type mice, and administration of NK-1R antagonist attenuates liver fibrosis in Mdr2 −/− mice and BDL mice [63].…”
Section: Pathways Associated With Cholangiocyte Responses and Theimentioning
confidence: 99%
See 1 more Smart Citation
“…This study has also demonstrated that SP administration elevates intracellular cAMP levels followed by cell proliferation in large cholangiocytes suggesting that the SP/NK-1R axis is associated with large cholangiocyte proliferation. A recent study has shown that serum levels of SP and NK-1R expression in the liver are elevated in human PSC patients compared to healthy individuals [63]. In addition, SP administration induces bile duct hyperplasia and liver fibrosis in wild-type mice, and administration of NK-1R antagonist attenuates liver fibrosis in Mdr2 −/− mice and BDL mice [63].…”
Section: Pathways Associated With Cholangiocyte Responses and Theimentioning
confidence: 99%
“…A recent study has shown that serum levels of SP and NK-1R expression in the liver are elevated in human PSC patients compared to healthy individuals [63]. In addition, SP administration induces bile duct hyperplasia and liver fibrosis in wild-type mice, and administration of NK-1R antagonist attenuates liver fibrosis in Mdr2 −/− mice and BDL mice [63]. These findings suggest that the SP/NK-1R axis plays a key role in bile duct proliferation and fibrosis in cholangiopathies.…”
Section: Pathways Associated With Cholangiocyte Responses and Theimentioning
confidence: 99%
“…SP is expressed by SI-NETs and is one of the kinins potentially involved in flushing and carcinoid heart disease (Vinik et al 1990, Facco et al 1998, Niederle et al 2016. Furthermore, SP acts as a profibrotic cytokine in inflammatory fibrotic diseases such as intestinal and liver fibrosis and NK1R antagonist have been found to counteract the SP-induced fibrosis and secretion of profibrotic growth factors such as TGFβ (Koon et al 2010, Wan et al 2017. Also, SP has a proliferative and promigratory effect in cancer (Esteban et al 2006).…”
Section: Other Growth Factorsmentioning
confidence: 99%
“…Also, SP has a proliferative and promigratory effect in cancer (Esteban et al 2006). NK1R antagonists are already in clinical use as antiemetic drugs and the recent research done in SP/NKR1 pathway in fibrosis and mitogenesis generated new interest in NK1R antagonist as an antitumour and antifibrotic treatment option (Esteban et al 2006, Wan et al 2017. However, the contribution of the SP/NKR1 pathway to development MF is unknown, and further research is essential before use of NK1R antagonist as antiproliferative and antifibrotic therapy can be considered.…”
Section: Other Growth Factorsmentioning
confidence: 99%
“…These considerations emphasize the importance of continued exploration of the cellular targets, molecular mechanisms, and pathophysiological consequences of cellular senescence in liver disease. In that context, Wan et al report on the intersection of the neuropeptide substance P (SP) and both cholangiocyte and myofibroblast senescence …”
mentioning
confidence: 99%